El estado de cosas inconstitucional: Aplicación, Balance y perspectivas - Aguilar Castillo, Juan Felipe; Bohorquez, Viviana; Santamaría Vecino, Claudia (Temas Socio-Jurídicos, 2014)
El estado de cosas inconstitucional: Aplicación, Balance y perspectivas